2019
DOI: 10.22377/ajp.v13i04.3397
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Context: Aqueous extract of cassava leaves (Manihot esculenta Crantz) has a high rutin content. Rutin has benefits as an antioxidant, anti-inflammatory, analgesic, and antidiabetic. The plant extract has low bioavailability and has a large molecular weight. Therefore, a carrier system like niosomes is required to allow aqueous leaves extract of cassava through to absorb in the body. Aims: The purpose of this study was to determine the effect of variation concentration of Span 40 that can trap aqueous extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In other works, it was reported that similar components produced from TW80 and CHOL were at 70% EE [40] and from SP60 and CHOL were at 71.29% EE [24]. Differences in the efficiency of drug encapsulation may depend on several factors, such as 3D chemical structure, hydrophilicity, the ratio of surfactant, and the structure of the surfactant [48,49]. In addition, the CHOL distributed between the lipid bilayer enhances encapsulation due to its membrane-stabilizing effect and the prevention of drug leakage [47,50].…”
Section: Discussionmentioning
confidence: 94%
“…In other works, it was reported that similar components produced from TW80 and CHOL were at 70% EE [40] and from SP60 and CHOL were at 71.29% EE [24]. Differences in the efficiency of drug encapsulation may depend on several factors, such as 3D chemical structure, hydrophilicity, the ratio of surfactant, and the structure of the surfactant [48,49]. In addition, the CHOL distributed between the lipid bilayer enhances encapsulation due to its membrane-stabilizing effect and the prevention of drug leakage [47,50].…”
Section: Discussionmentioning
confidence: 94%